Profitabilitas sebagai Pemoderasi Pengaruh Struktur Aktiva, Risiko Bisnis, dan Ukuran Perusahaan pada Struktur Modal - Wulandari, Ni Made Arika; Sari, Maria Mediatrix Ratna (E-Jurnal Akuntansi; Vol 31 No 9 (2021)DO - 10.24843/EJA.2021.v31.i09.p05, 2021)
The capital structure is very important for the company, this is because it involves the policy of determining the source of funding used, both from inside and outside the company. This study aims to determine the effect of asset structure, business risk, and firm size on capital structure with profitability as a moderating variable. The research was conducted on manufacturing sector entities that are listed on the Indonesia Stock Exchange (IDX) for the 2016-2019 period. The population is 141 entities. Based on the purposive sampling method, the research sample used was 70 manufacturing entities. The data analysis technique in this study is moderated regression analysis. The results showed that the asset structure has a negative effect on the capital structure. Business risk has no influence on the capital structure. Firm size has a positive influence on capital structure. Profitability is able to moderate the effect of asset structure and firm size on capital structure. Profitability does not moderate the effect of business risk on capital structure. Keywords: Capital Structure; Assets Structure; Business Risk; Firm Size; Profitability.